Self and social regulation : social interaction and the development of social understanding and executive functions - Sokol, Bryan W. (New York ; Oxford : Oxford University Press, 2010)
Does social interaction play a role in the development of executive function or, more generally, self-regulation? If it does play a role, what forms of social interaction facilitate the development of executive function? In this book, the contributors address these questions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social perception in children; Social interaction in children; Cognition in children